Solid waste from health services and the environment: perception of the nursing team - Ilisdayne Thallita Soares da Silva; Diego Bonfada (Universidade Federal do Ceará, 2012)
This study aimed to analyze the perception about the environmental impact of the production process of solid waste from health services of the nursing staff at a hospital in Santa Cruz. Qualitative research conducted in the period March-April 2010. Data were collected through interviews with 17 nurses and analyzed using thematic analysis. The data analysis demonstrated the production of solid wastes, along with the nursing procedures in your workspace. There was also a need for training on the solid waste from health services security-oriented environment, which indicates that knowledge by the nursing staff about this subject is still new, contributing to negative impacts on the environment are generated. Therefore, it is essential to invest in training that involves a process of continuing education, contributing to the consolidation of environmentally responsible values, to promote quality of life associated with sustainability and preservation.